Shifts in EU Cohesion Policy and Processes of Peripheralization: A View from Central Eastern Europe - Faragó, László; Varró, Krisztina (European Spatial Research and Policy, 2016)
The increasing dominance of neoliberalism as the key steering mechanism of the European Union (EU) since the early 1990s has implied the competitiveness-oriented reshaping of cohesion policy. The aim of this paper is to initiate a debate from a critical political economic perspective on the implications of this shift for Central Eastern European (CEE) member states. To this end, the paper discusses the formation of EU centre-periphery relations from a CEE point of view and formulates some preliminary suggestions as to how cohesion policy would need to be rethought in order to ensure the better integration of lagging CEE regions.